2007
DOI: 10.1108/09596110710747625
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the cost of quality in a hotel restaurant operation

Abstract: Purpose -The objective of this research is to apply the cost of quality (COQ) concepts in a hotel restaurant environment using the PAF (prevention, appraisal, and failure costs) model. Then use the percentage of sales approach to evaluate the significance of the COQ measures in the PAF model. Design/methodology/approach -This research involved reviewing available literature on the COQ framework. Then through the process of interviews and secondary data collection, an analysis of the COQ measures in the PAF mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 14 publications
1
29
1
2
Order By: Relevance
“…Specifically, the authors investigated the degree of tolerance for socially deviant employee behaviors. Previous research has demonstrated that service failures caused by deviant employee behavior can lead to economic losses (Murphy 1993;Ramdeen et al 2007), customer dissatisfaction (Bitner et al 1990), negative word of mouth (HarrisonWalker 2001), and customer switching behavior (Keaveney 1995). Recent research in service recovery demonstrates the need for understanding personality traits when examining consumer reactions to service failures (Mittal et al 2008).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Specifically, the authors investigated the degree of tolerance for socially deviant employee behaviors. Previous research has demonstrated that service failures caused by deviant employee behavior can lead to economic losses (Murphy 1993;Ramdeen et al 2007), customer dissatisfaction (Bitner et al 1990), negative word of mouth (HarrisonWalker 2001), and customer switching behavior (Keaveney 1995). Recent research in service recovery demonstrates the need for understanding personality traits when examining consumer reactions to service failures (Mittal et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Previous research has demonstrated that service failures caused by deviant employee behavior can result in substantial losses for the company (Murphy 1993). Employee-related service failures have been shown to lead to customer dissatisfaction (Bitner, Booms, and Tetreault 1990), negative word of mouth (Harrison-Walker 2001), customer switching behavior (Keaveney 1995), and revenue loss (Ramdeen, Santos, and Chatfield 2007).…”
Section: Introductionmentioning
confidence: 99%
“…1 proposes that mindfulness implementations are preventative measures and lead to increased (P) costs that result in reduced process variance, increased reliability, and reduced defects. Although other healthcare-related studies use PAF (i.e., Ramdeen et al, 2007;McLaughlin and Kaluzny, 2004, p. 32), this study is the first to examine the relationship between mindfulness, process variance, and costs using PAF. This framework necessitates the examination of a possible direct effect of mindfulness on process variance.…”
Section: Literature Reviewmentioning
confidence: 96%
“…For instance, Johnson and Chambers (2000) identified benchmarking as a continuous, systematic management process that enables food and beverage managers to ascertain current practice. In a recently conducted study, Ramdeen et al (2007) measured cost of quality (COQ) concepts in a hotel restaurant environment over a 2-year period using the prevention, appraisal and failure (PAF) model. Their findings indicated that COQ accounts for 12-16% of sales.…”
Section: Hotel Food Controlmentioning
confidence: 99%
“…Overproduction and inadequate purchasing both lead to costly food wastage (Hu, Chen, & McCain, 2004), affecting a hotel's food costs and inevitably its bottom line. Hotel restaurants also need to maintain the quality of food and services to retain or increase customer satisfaction levels and ultimately boost profitability (Ramdeen, Stantos, & Chatfield, 2007). Ramdeen et al (2007) suggested it is necessary to allocate more resources to prevention activities such as quality training and supplier evaluation.…”
Section: Introductionmentioning
confidence: 99%